Abusive Supervision in Southeast Asia Countries: : A Viewpoint of Trends and Future Research Directions - Hillman Wirawan; Muhammad Tamar; Uswatun Hasanah Nurkholis (International Journal of Educational Administration, Management, and Leadership, 2025)
This viewpoint article reviews the evolving trends of abusive supervision studies across Southeast Asian countries. This article employs a traditional literature review by synthesizing references from various leading research databases. Abusive supervision is destructive and can cause adverse impacts on employees and organizations. It poses significant challenges to employee and organizational well-being. While extensive research has been documented in various Western contexts, scientific evidence related to abusive supervision in Southeast Asia remains underexplored. Southeast Asian people are characterized by a unique interplay of collectivist orientations and hierarchical power distance that may shape the tolerance, perception, and consequences of supervisory abuse. This article proposes that organizational silence and strong respect for authority figures have contributed to the emergence and persistence of abusive supervision in Southeast Asian regions. Furthermore, societal norms such as filial piety and face-saving behaviors may obscure recognition and resistance to such abuse. This article identifies several research gaps by integrating information from cultural and organizational insights. Firstly, future studies should anchor research directions with cultural values, and secondly, human resource and leadership practices must be tailored to Southeast Asian contexts. Understanding the influence of regional context on the development of abusive supervision is critical for designing responsive leadership development. This article urges context-sensitive empirical studies and collaborative human resource practices to reduce the emergence of supervisory abuse in the region.